Study on bivalent attenuated vaccine of infectious bursal disease virus variants - ZHOU Ji-yong; LI Jian-rong (浙江大学学报. 农业与生命科学版)
For detecting their immunogenicity and security, infectious bursal disease virus (IBDV) “JN” and “JH” bivalent live vaccine were vaccinated into 14 day old SPF chickens at three different doses (6 000 TCID50、10 000 TCID50、20 000 TCID50) after the different time of primary and secondary immunization for experimental challenge studies with a virulent IBDV strain BC6/85 respectively. The results show that SPF chickens are secure and have better immune responses to JH and JN vaccines, while the protection of the vaccinated chickens was 100% after challenge with the virulent IBDV-BC6/85. The optimal dose was 6 000 TCID50 for JN vaccine and 10 000 TCID50 for JH vaccine.